Penerapan Evaluasi Model Ekop dalam Pembelajaran Terpadu Mata Kuliah Sejarah Asia Selatan - Musa Pelu (LPPM Press, 2010)
Abstract: this research has a purpose to plan and apply the evaluation of EKOP model inintegrated teaching of Connected model to increase the teaching quality of the South AsiaHistory 2 lecture at the Historical Program of FKIP UNS. The subjects of the research are thestudents who study the South Asia History 2 lecture at the even semester in 2009/2010Academic Year. The research is done by using the classroom action research method (PTK).The technique and equipment which are used to get the data in the research are thequestionnaire technique, observation, and interview. The result of the research shows that theapplication of EKOP model evaluation in the integrated teaching of connected model canincrease the teaching quality of South Asia History 2 lecture. It is shown by the scores averageof teaching quality components at numbers 3.4 – 4.1 which are categorized as good in the firstcycle and the second cycle. The total scores average are categorized as good on the numbers3.51 at the first cycle and 3.57 at the second cycle.